To Drug or not to Drug: The Treatment of Social Anxiety Disorder - Aoun, Raquel; Downey, Mackenzie (Université d'Ottawa | University of Ottawa, 2017)
Background: Social anxiety disorder (SAD), also known as social phobia, is the extreme anxiety or fear of being judged by others in socials situations. Conditions that initiate these feelings are ones in which the individual is observed, must socially interact, or perform in front of others. This fear of negative evaluation leads to a person avoiding social interaction, which can have negative implications in everyday life. The DSM-5 states that abstinence of social situations caused by the fear or anxiety of scrutiny from others must occur for 6 months or more. This avoidance must cause distress or impairment, and not be due to the substance use, another mental disorder, or medical condition. In Canada, lifetime prevalence is between 8% and 13%, with a higher risk for women. Onset is typically seen during early adolescence and depreciates later in life. Objective: The aim of this study is to discover the etiology, diagnosis, and treatment options for those living with SAD. Moreover, the effect of the disorder on quality of life, including quality-adjusted life years (QALY) and disability-adjusted life years (DALY) will also be evaluated. Methodology: To collect the following information, an online search with a restriction of 10 years from today’s date was implemented, along with the use of the newest edition of the textbook Abnormal Psychology to ensure the most current results. Search engines included Google Scholar, Statistics Canada, and Pubmed database to which SAD and only one category (ex. etiology) was researched to guarantee concise, detailed information. Results: SAD is caused by the interaction of biological, psychological, and social vulnerabilities. Individuals born with temperamental profiles inherit the trait of inhibition/shyness. Furthermore, factors such as low socioeconomic status, and possessing comorbid major depressive disorder display higher rates of SAD. Canadians afflicted with SAD were twice as likely to record at least one disability within the past two weeks compared to those without. Also, social phobia has been associated with a co-morbidity rate of 72%. Long-term cognitive behavioural therapy (CBT) is considered the ideal treatment with first, second and third-line agents as pharmacological interventions. Conclusion: Social phobia is a highly prevalent anxiety disorder associated with many problems, including familial life, economic burden and academic and occupational performance. As a result, SAD poses a significant risk on quality of life for those afflicted and society because of missed workdays and healthcare costs. Further research should be conducted to improve the quality of life of Canadians affected.